2017
DOI: 10.1038/srep46380
|View full text |Cite
|
Sign up to set email alerts
|

Genetic visualization of protein interactions harnessing liquid phase transitions

Abstract: Protein-protein interactions (PPIs) are essential components of cellular function. Current fluorescence-based technologies to measure PPIs have limited dynamic range and quantitative reproducibility. Here, we describe a genetically-encoded PPI visualization system that harnesses the dynamics of condensed liquid-phase transitions to analyze protein interactions in living cells. The fluorescent protein Azami-Green and p62-PB1 domain when fused to PPI partners triggered a rapid concatenation/oligomerization proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 49 publications
0
71
0
Order By: Relevance
“…Indeed, a recent report indicates that interactions between ATG8 proteins and the LIR motif in OPTN (and NDP52) drive additional recruitment of OPTN (and NDP52) to the growing autophagic membrane through an ATG8-dependent positive feedback loop (Padman et al, 2019). To monitor the binding of ATG8 proteins to the autophagy adaptors in cells, we used the protein-protein interaction technology termed Fluoppi (Koyano et al, 2014;Watanabe et al, 2017;Yamano et al, 2015). An Ash tag, which forms a homooligomer, was fused to linear 6Ub (WT or K0), and a homotetrameric humanized Azami-Green (hAG) tag was fused to the autophagy adaptors ( Fig.…”
Section: Generation Of Phase-separated Foci Composed Of Linear Ub Chamentioning
confidence: 99%
“…Indeed, a recent report indicates that interactions between ATG8 proteins and the LIR motif in OPTN (and NDP52) drive additional recruitment of OPTN (and NDP52) to the growing autophagic membrane through an ATG8-dependent positive feedback loop (Padman et al, 2019). To monitor the binding of ATG8 proteins to the autophagy adaptors in cells, we used the protein-protein interaction technology termed Fluoppi (Koyano et al, 2014;Watanabe et al, 2017;Yamano et al, 2015). An Ash tag, which forms a homooligomer, was fused to linear 6Ub (WT or K0), and a homotetrameric humanized Azami-Green (hAG) tag was fused to the autophagy adaptors ( Fig.…”
Section: Generation Of Phase-separated Foci Composed Of Linear Ub Chamentioning
confidence: 99%
“…In principle, the PPI of interest can serve as either the scaffold or the client. In the former setup, both partners of the PPI are multimerized via fusion to homo-oligomeric proteins and the appearance of phase-separated puncta serves as a readout for the interaction 20,21,40 . This strategy is adopted by two recent work, Fluoppi 20 and SPARK 21 .…”
Section: Discussionmentioning
confidence: 99%
“…First, we sought to establish some multivalent scaffolds that can robustly drive the formation of compartments via LLPS. Numerous studies have demonstrated that interactions between linear and/or dendrimeric (branched) multivalent modular proteins can result in LLPS 17,[19][20][21][22] . The Saccharomyces cerevisiae protein SmF (referred to as SmF hereafter) is known to form a stable tetradecameric (referred to as 14-meric for simplicity hereafter) complex upon expression alone in bacteria 23 .…”
Section: Establishing Robust Multivalent Scaffoldsmentioning
confidence: 99%
“…Aittaleb and colleagues used BiFC to study interactions between several DGC components at murine NMJs . Novel tools have been recently implemented to optically induce phase transition in living cells and study protein–protein interactions because of their ability to induce the formation of protein droplets . Additionally, sophisticated statistical analyses allow elucidation of the hierarchy of synergic interactions within multimolecular assemblies .…”
Section: Is Assembly Of the Dgc An Example Of A Phase Separation Phenmentioning
confidence: 99%